IMPLEMENTASI PERATURAN MAHKAMAH AGUNG TENTANG TATA CARA PENYELESAIAN GUGATAN SEDERHANA DI PENGADILAN NEGERI BENGKULU - Dimas Dwi Arso; Slamet Muljono; Edytiawarman Edytiawarman; Nurhani Fithriah (TANJUNGPURA LAW JOURNAL, 2023)
AbstractSettlement of disputes in society can be resolved through the courts. Currently, there is a Supreme Court Regulation Concerning Procedures for Settlement of Simple Claims. Simple lawsuits are mild civil lawsuits with a fast case settlement process. Several restrictions have been regulated in this supreme court regulation. This is because this simple lawsuit case is designed to find a quick and straightforward solution to the legal issues faced by the parties so that a protracted settlement of claims does not occur and the payment of cases is resolved based on the principle of a fast, simple, and low-cost trial. This study aims to identify and analyze the implementation of supreme court regulation concerning Procedures for the Settlement of Simple Claims at Class IA Bengkulu District Court. The research method is carried out by empirical juridical research. The study results are the Implementation of Supreme Court Regulation concerning Procedures for Settlement of Simple Claims at the Class I Bengkulu District Court, carried out by existing regulations such as for the settlement of unlawful acts or defaults with a maximum lawsuit of Rp.500.000.000,- (Five hundred million rupiah) and settled by a single judge.However, for dispute resolution, the judge may decide more than 25 days by the supreme court regulation provisions because the judge needs more time to seek peace and give a decision to the parties in settlement of a simple lawsuit. Then the obstacle faced in the payment of a simple lawsuit at the Class I Bengkulu District Court is during the peace process when the plaintiff and the defendant do not have the same nominal value to be paid; it could be because the defendant is unable to pay off the default claim or unlawful act. AbstrakPenyelesaian sengketa dalam masyarakat dapat diselesaikan melalui pengadilan. Saat ini, telah ada Peraturan Mahkamah Agung yang mengatur Tentang Tata Cara Penyelesaian Gugatan Sederhana. Gugatan perdata ringan dengan proses penyelesaian perkara cepat merupakan gugatan sederhana. Perma ini sudah mengatur beberapa pembatasan. Karena, penyelesaian gugatan sederhana ini merupakan gagasan guna menjadi solusi dari masalah hukum melibatkan para pihak dengan sederhana dan cepat guna tidak terjadi proses yang lama dalam penyelesaian sengketa dan penyelesaian perkara diselesaikan berdasarkan prinsip peradilan cepat, sederhana, dan biaya ringan. Penelitian ini bertujuan guna menganalisis implementasi Perma tentang Tata Cara Penyelesaian Gugatan Sederhana di Pengadilan Negeri Kelas IA Bengkulu. Metode penelitian yuridis sosiologis digunakan dalam penelitian ini. Adapun hasil penelitian yaitu Implementasi Peraturan Mahkamah Agung tentang Cara Penyelesaian Gugatan Sederhana di Pengadilan Negeri Kelas IA Bengkulu yaitu dilaksanakan dengan sesuai regulasi seperti untuk penyelesaian kasus wanprestasi atau perbuatan melawan hukum dengan gugatan maksimal Rp. 500.000.000,- (lima ratus juta rupiah) dan diselesaikan oleh hakim tunggal. Namun,untuk penyelesaian sengketa bisa saja hakim memutuskan lebih dari 25 hari sesuai dengan ketentuan Perma sebab hakim membutuhkan waktu yang lebih lama untuk mengupayakan perdamaian dan memberikan putusan kepada para pihak dalam acara peradilan gugatan sederhana. Kendala yang dihadapi melalui proses gugatan sederhana di Pengadilan Negeri Kelas IA Bengkulu yakni saat proses perdamaian bilamana antara penggugat dan tergugat tidak ada persamaan nilai nominal yang harus dibayarkan, bisa jadi karena tergugat tidak mampu melunasi gugatan perbuatan melawan hukum atau wanprestasi.